Ticagrelor in Triple Antithrombotic Therapy: Predictors of Ischemic and Bleeding Complications. Issue 1 (8th January 2016) - Fu, Angel; Singh, Kuljit; Abunassar, Joseph; Malhotra, Nikita; Le May, Michel; Labinaz, Marino; Glover, Christopher; Marquis, Jean‐Francois; Froeschl, Michael; Dick, Alexander; Hibbert, Benjamin; Chong, Aun‐Yeong; et al.
ABSTRACT: Background: Patients on dual antiplatelet therapy following percutaneous coronary intervention often have indications for concurrent oral anticoagulation or triple antithrombotic therapy (TT). Although TT may decrease ischemic complications, it may confer increased bleeding risk. Hypothesis: We hypothesize that the use of ticagrelor in TT is associated with higher risk of complications; accordingly, we sought to determine predictors of complications in patients on TT. Methods: Patients discharged on TT after percutaneous coronary intervention were followed prospectively for 12 months. The primary endpoint was a composite of ischemic (death, myocardial infarction, stroke) and major bleeding complications or net adverse clinical event (NACE). A major secondary endpoint was BARC (Bleeding Academic Research Consortium) types 2, 3, or 5 bleeding. Outcomes were compared between ticagrelor‐ and clopidogrel‐treated patients. Multivariable analyses were performed to elucidate predictors of complications. Results: Twenty‐seven of 152 patients discharged on TT were on ticagrelor. NACE occurred in 52% of patients and BARC 2, 3, or 5 bleeding occurred in 18%. There was no difference in the primary or secondary outcome between ticagrelor vs clopidogrel subgroup. On logistic regressions, use of TT in patients with acute coronary syndrome ( P = 0.002) and bridging in with ticagrelor ( P = 0.02) were associated with increased NACE. Low estimated glomerular filtration rate was an independent predictor of bleeding ( P = 0.03). Conclusions: The risk of bleeding and ischemic complications among patients on TT is similar between those on ticagrelor and clopidogrel. However, caution with use of bridging anticoagulation should be taken when using ticagrelor.